Delivering LINE1 antisense oligonucleotides via endothelial targeting extracellular vesicles to ameliorate myocardial infarction-induced cardiac senescence - Enze Fu; Kai Pan; Benjamin Hinnant; Shang Chen; Zhibo Han; Zhikun Guo; Zhong-chao Han; Qiong Li; Zongjin Li (Bioactive Materials)
Transposable elements (TEs) constitute a significant portion of the nuclear genome, but their influence on and ability to manage their activity during tissue regeneration remain largely unknown. Here, we revealed that LINE1, the most abundant TE, responds to cardiomyocyte injury and is overexpressed in a myocardial infarction (MI) model. We developed selectin binding peptide (SBP)-engineered extracellular vesicles (EVs) with targeted functions, which are loaded with LINE1 antisense oligonucleotide (ASO). The engineered EVs display targeted accumulation in injured hearts and protect against myocardial senescence by inhibiting the cGAS-STING‐TBK1‐IRF3 pathway and suppressing the expression of senescence-associated secretory phenotype (SASP) factors. Our data revealed that LINE1 retrotransposon activation is triggered by cardiomyocyte injury in the MI model. We also propose a strategy to reduce cardiomyocyte senescence post-myocardial infarction by modulating LINE1 activity.